Kajian Efektivitas Fungsi Taman Kota Raja Sebagai Ruang Terbuka Hijau Publik Berdasarkan Persepsi Pengunjung - Sandi, Virna Adha Febriana; Pratiwi, Dwinsani; Mustofa, Umar; Depari, Andi Sahputra (COMPACT: Spatial Development Journal, 2024)
City parks are part of public green open spaces whose effectiveness can be assessed through the functions of city parks. Kota Raja Park is one of the city parks in Tenggarong Sub-district whose existence is considered as an aesthetic function of the city even though the city park has other functions to be able to make it a successful public green open space. However, there has been no measurable research on the effectiveness of Taman Kota Raja as a public open space in Tenggarong District which can be used to see the performance of the city park function. Based on this, the researcher has the aim of knowing the level of effectiveness of Taman Kota Raja in Tenggarong District as a public green open space. The analysis in this study used scoring analysis with a rating scale on indicators and variables. The results of the scoring analysis show that the overall function of Taman Kota Raja is included in the effective category with the socio-cultural function having an effectiveness value of 2.5; the aesthetic function has an effectiveness value of 2.51; and the economic function has an effectiveness value of 2.57. The research shows that the economic function is the most effective function where economic activities and facilities in the park are rated very well by visitors. Based on age groups, the variables of cultural expression activities, park infrastructure design, and park accessibility are variables that have the best effectiveness value. Keywords : effectiveness, fuctions of city parks, public green open space